Mcr-1 and mcr-2 (mcr-6.1) variant genes identified in Moraxella species isolated from pigs in Great Britain from 2014 to 2015. (11th August 2017) - AbuOun, Manal; Stubberfield, Emma J; Duggett, Nick A; Kirchner, Miranda; Dormer, Luisa; Nunez-Garcia, Javier; Randall, Luke P; Lemma, Fabrizio; Crook, Derrick W; Teale, Christopher; Smith, Richard P; Anjum, Muna F
Abstract: Objectives: To determine the occurrence of mcr-1 and mcr-2 genes in Gram-negative bacteria isolated from healthy pigs in Great Britain. Methods: Gram-negative bacteria ( n = 657) isolated from pigs between 2014 and 2015 were examined by WGS. Results: Variants of mcr-1 and mcr-2 were identified in Moraxella spp . isolated from pooled caecal contents of healthy pigs at slaughter collected from six farms in Great Britain. Other bacteria, including Escherichia coli from the same farms, were not detected harbouring mcr-1 or mcr-2 . A Moraxella porci -like isolate, MSG13-C03, harboured MCR-1.10 with 98.7% identity to MCR-1, and we describe the first detection of mcr-6.1, found on the chromosome of Moraxella pluranimalium, with 87.9% identity to MCR-2 from E. coli . The Moraxella isolates had colistin MICs of 1–2 mg/L. No intact insertion elements were identified in either MSG13-C03 or MSG47-C17, although MSG13-C03 harboured the conserved nucleotides abutting the IS Apl1 composite transposon found in E. coli plasmids and the intervening ∼2.6 kb fragment showed 97% identity. Six Moraxella osloensis isolates were positive for phosphoethanolamine transferase (EptA). They shared 62%–64.5% identity to MCR-1 and MCR-2, with colistin MICs from 2 to 4 mg/L. Phylogenetic analysis indicated that MCR and EptA have evolved from a common ancestor. In addition to mcr, the β-lactamase gene, bla BRO-1, was found in both isolates, whilst the tetracycline resistance gene, tetL, was found in MSG47-C17. Conclusions: Our results add further evidence for the mobilization of the mcr-pap2 unit from Moraxella via composite transposons leading to its global dissemination. The presence of mcr-pap2 from recent Moraxella isolates indicates they may comprise a reservoir for mcr .